The social impact of schooling on students with dyslexia: A systematic review of the qualitative research on the primary and secondary education of dyslexic students. (February 2023) - Nevill, Thom; Forsey, Martin
Abstract: This systematic review of the qualitative research on the formal school education of children with dyslexia addresses three main questions: 1) What is known about the educational experiences of children with dyslexia? 2) What is known about the role that parents/guardians play in their child's schooling? 3) What is known about the role of teachers and administrators in supporting children with Dyslexia? Student and parent-focused studies indicate little awareness of and support for dyslexia in schools, and a strong reliance on parental support. Limited understanding of dyslexia, lack of training, and communication issues were identified as key themes in the small number of teacher-focused studies. The analysis points to a majority of studies not having a firm theoretical grounding and the neglect of teachers and school administrator's perspectives as central issues in the reviewed research. Based on these findings, it is argued that to further understandings of the systematic effects of schools' responses to dyslexic students, research should draw more heavily on socio-cultural models of disability. Highlights: This article focuses on the schooling experiences of students diagnosed with dyslexia, the experiences of parents with children diagnosed with dyslexia and the perspectives of key-stakeholders in schools on supporting these students. The article provides the first systematic review of the corpus of published, peer reviewed qualitative research on the primary and secondary schooling of dyslexic students. The key findings emerging from this review strongly indicate that school systems are struggling to adequately support the needs of dyslexic students.